A de novo Loss-of-function Variant in RAPGEF6 Supports its Role in Neuropsychiatric Disorders - Simone Treccarichi; Mirella Vinci; Maria Grazia Figura; Antonino Musumeci; Miriam Virgillito; Carla Papa; Valeria Chiavetta; Desiree Brancato; Francesca Bruno; Concetta Federico; Justin Simo; Roberta La Piana; et al. (Journal of Molecular Neuroscience, 2026)
RAPGEF6 is a member of the guanine nucleotide exchange factor (GEF) subfamily that acts on Rap small GTPases and contains a Ras/Rap-associating domain. Although deficiency of this gene has previously been linked to schizophrenia, no MIM phenotype entry currently associates RAPGEF6 with a defined clinical condition. In this study, trio-based whole-exome sequencing (WES) was performed in an individual presenting with psychiatric disorders and mild intellectual disability. WES revealed a de novo frameshift variant, c.272dup (p.Pro92Serfs*6), in the RAPGEF6 gene (NM_016340.6). This variant was classified as likely pathogenic according to ACMG criteria. Nonetheless, the contribution of additional genetic factors not detected by WES cannot be excluded. According to developmental transcriptomic data from the BrainSpan database, RAPGEF6 is expressed in the human brain across the entire lifespan and participates in neuron projection development, Rap-protein signal transduction, and regulation of GTPase activity. Structural variation data from DECIPHER further indicate that copy-number variants involving RAPGEF6 are primarily associated with intellectual disability and micrognathia. In addition, DECIPHER shows that RAPGEF6 is highly intolerant to loss-of-function (LoF) variants. Both NMD-Esc predictor and Mutation Taster suggest that the identified frameshift mutation is likely to trigger nonsense-mediated decay (NMD) of the RAPGEF6 transcript, resulting in loss of protein production. In addition, RAPGEF6 expression progressively increased during retinoic acid-induced neuronal differentiation of SK-N-BE neuroblastoma cells, supporting a potential role of this gene in neuronal maturation processes. Together, these data support a contributory role of RAPGEF6 haploinsufficiency in neurodevelopmental and psychiatric phenotypes, reinforcing its emerging relevance in neuropsychiatric disorders.

Development of a pro-arrhythmic ex vivo intact human and porcine model: cardiac electrophysiological changes associated with cellular uncoupling - Joseph Brook; Min-young Kim; Simos Koutsoftidis; David Pitcher; Danya Agha-Jaffar; Annam Sufi; Catherine Jenkins; Konstantinos Tzortzis; Suofeiya Ma; Richard J. Jabbour; Charles Houston; Balvinder S. Handa; et al. (Pflügers Archiv - European Journal of Physiology, 2020)
We describe a human and large animal Langendorff experimental apparatus for live electrophysiological studies and measure the electrophysiological changes due to gap junction uncoupling in human and porcine hearts. The resultant ex vivo intact human and porcine model can bridge the translational gap between smaller simple laboratory models and clinical research. In particular, electrophysiological models would benefit from the greater myocardial mass of a large heart due to its effects on far-field signal, electrode contact issues and motion artefacts, consequently more closely mimicking the clinical setting. Porcine ( n = 9) and human ( n = 4) donor hearts were perfused on a custom-designed Langendorff apparatus. Epicardial electrograms were collected at 16 sites across the left atrium and left ventricle. A total of 1 mM of carbenoxolone was administered at 5 ml/min to induce cellular uncoupling, and then recordings were repeated at the same sites. Changes in electrogram characteristics were analysed. We demonstrate the viability of a controlled ex vivo model of intact porcine and human hearts for electrophysiology with pharmacological modulation. Carbenoxolone reduces cellular coupling and changes contact electrogram features. The time from stimulus artefact to (-dV/dt) max increased between baseline and carbenoxolone (47.9 ± 4.1–67.2 ± 2.7 ms) indicating conduction slowing. The features with the largest percentage change between baseline and carbenoxolone were fractionation + 185.3%, endpoint amplitude − 106.9%, S-endpoint gradient + 54.9%, S point − 39.4%, RS ratio + 38.6% and (-dV/dt) max − 20.9%. The physiological relevance of this methodological tool is that it provides a model to further investigate pharmacologically induced pro-arrhythmic substrates.

Secondary metabolites with antiproliferative effects from Albizia glaberrima var glabrescens Oliv. (Mimosoideae) - Ghislain Wabo Fotso; Justin Kamga; Bathelemy Ngameni; Shota Uesugi; Misa Ohno; Ken-Ichi Kimura; Hiroyuki Momma; Eunsang Kwon; Hiroshi Furuno; Yoshihito Shiono; Simo K. Ingrid; Samuel O. Yeboah; et al. (Natural Product Research, 2017)